PENGGUNAAN MOMBI DALAM PEMBELAJARAN HUKUM II NEWTON DI SMA NEGERI 1 AMURANG - Rarung, Agnes E. S; Tumangkeng, Jeane V; Mongan, Satyano W. (LPPM Politeknik Saint Paul Sorong, 2024)
Model of Model-Based Instruction (MOMBI) is a learning model that emphasizes the formation of mental models through the stages of provocation, preconcept, presentation, scaffolding, and practice. The aim of this research is to determine the use of MOMBI in improving students’ learning results in Newton's Second Law material at SMA Negeri 1 Amurang. The method used in this research was quasi-experimental method with a pretest-posttest control group design. The sample for this study was taken randomly with XI-H students as the experimental class with MOMBI treatment and XI-I students as the control class. Data was collected using essay tests and observation. The data obtained was then analyzed statistically. Based on the average results of the pretest and posttest for the control class, the average pretest value was 39.44 and the average posttest value was 56.67. A higher increase was obtained in the experimental class with an average pretest score of 41.67 and an average posttest score of 78.89. So it can be concluded that the Model of Model-Based Instruction can improve student’s learning results in Newton's Second Law at SMA Negeri 1 Amurang